2018
DOI: 10.1097/md.0000000000012154
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of epidemiology, presentation, and management of Meckel's diverticulum in the 21st century

Abstract: The epidemiological patterns and clinical presentation appears stable in the 21st century. A symptomatic Meckel's diverticulum is managed by resection. The issue of prophylactic in incidental Meckel's diverticulum resection remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
308
3
48

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(368 citation statements)
references
References 57 publications
9
308
3
48
Order By: Relevance
“…Although it is universally accepted that a complicated MD must be removed, the resection of an incidentally discovered uncomplicated MD remains controversial . Zani et al reported a complication rate of 1.3% in incidentally discovered uncomplicated MDs left in situ compared to a complication rate of 5.3% after resection and opposed resection .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is universally accepted that a complicated MD must be removed, the resection of an incidentally discovered uncomplicated MD remains controversial . Zani et al reported a complication rate of 1.3% in incidentally discovered uncomplicated MDs left in situ compared to a complication rate of 5.3% after resection and opposed resection .…”
Section: Discussionmentioning
confidence: 99%
“…Analogous studies opposed the resection of an incidentally discovered uncomplicated MD . Other studies reported a 1.2–2% complication risk after MD resection compared with a lifetime morbidity risk 6.4–7% and recommended resection of all MDs encountered . The reported association of MD with intestinal cancer in adulthood impelled the tendency towards resection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meckel's diverticulum represents a remnant of the omphalomesenteric duct, which results from the failure of the duct to obliterate during the 5 th -7 th gestational week [1]. It is identified in 0.3-2.9% of the general population, whereas complications develop in 4.2-9.0% of the affected patients [2,3]. Tc 99m scintigraphy constitutes the most widely used imaging modality, with sensitivity and specificity of 80-100% and 50-100%, respectively [3].…”
mentioning
confidence: 99%
“…It is identified in 0.3-2.9% of the general population, whereas complications develop in 4.2-9.0% of the affected patients [2,3]. Tc 99m scintigraphy constitutes the most widely used imaging modality, with sensitivity and specificity of 80-100% and 50-100%, respectively [3].…”
mentioning
confidence: 99%